2019
DOI: 10.1109/tifs.2018.2849978
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Feedback Coding Scheme for the Wire-Tap Channel

Abstract: The model of wiretap channel (WTC) is important as it constitutes the essence of physical layer security (PLS). Wiretap channel with noiseless feedback (WTC-NF) is especially interesting as it shows what can be done when a private feedback is available. The already existing secret key based feedback coding scheme focuses on generating key from the feedback and using this key to protect part of the transmitted message. It has been shown that this secret key based feedback coding scheme is only optimal for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Inspired by the above WZ scheme, [60] proposed a new feedback scheme for the general WTC, which combines the secret key-based feedback scheme [15] and the WZ scheme [59]. This scheme is described below.…”
Section: New Results On the General Wtc With Noiseless Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the above WZ scheme, [60] proposed a new feedback scheme for the general WTC, which combines the secret key-based feedback scheme [15] and the WZ scheme [59]. This scheme is described below.…”
Section: New Results On the General Wtc With Noiseless Feedbackmentioning
confidence: 99%
“…To be specific, in [61], the broadcast channel with two confidential messages and noiseless feedback [61] was investigated, where a transmitter wishes to send two independent messages to two receivers via a general broadcast channel, each receiver can successfully decode its intended message and attempts to overhear the other one's intended message, and the receivers send their received signals back to the transmitter via two independent noiseless feedback channels. For this extended model, a new feedback scheme which is an extension of the improved secret key-based feedback scheme for the WTC with noiseless feedback [60] is proposed, and it combines a generalized WZ scheme [62] (see Fig. 3) for the distributed source coding with side information problem 3 , the secret key-based feedback scheme [15] and the coding scheme for the broadcast channel with two confidential messages 3 The generalized WZ scheme shown in Fig.…”
Section: Applications Of the Improved Secret Key-based Feedback Schemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, [9] presented an achievable scheme for the wiretap channel with generalized feedback, which is a generalization and unification of several relevant previous results in the literature. Very recently, [10] proposed an improved feedback coding scheme for the wiretap channel with noiseless feedback, which was shown to outperform the existing ones in the literature. A more comprehensive review of the previous work can be found in the extended version of this paper [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, [27] presented an achievable scheme for the wiretap channel with generalized feedback, which is a generalization and unification of several relevant previous results in the literature. Very recently, [28] proposed an improved feedback coding scheme for the wiretap channel with noiseless feedback, which was shown to outperform the existing ones in the literature.…”
mentioning
confidence: 99%